Effect of triples to dipole moments in fock-space multireference coupled cluster method - Ravichandran, Lalitha; Vaval, Nayana; Pal, Sourav (Journal of Chemical Theory and Computation, 2011)
In this paper, we present the new implementation of partial triples for the dipole moment of doublet radicals in Lagrangian formulation of Fock-space multireference coupled cluster (A-FSMRCC) response method. We have implemented a specific scheme of noniterative triples, in addition to singles and doubles schemes, which accounts for the effects appearing at least at the third order in dipole moments. The method is applied to the ground states of OH, OOH, HCOO, CN, CH, and PO radicals.

Equation-of-motion coupled-cluster method for the study of shape resonance - Ghosh, Aryya; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2012)
The equation-of-motion coupled-cluster method (EOM-CC) is applied for the first time to calculate the energy and width of a shape resonance in an electron-molecule scattering. The procedure is based on inclusion of complex absorbing potential with EOM-CC theory. We have applied this method to investigate the shape resonance in e(-)N(2), e(-)CO, and e(-)C(2)H(2). (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4729464]

Extended coupled cluster for Raman and infrared spectra of small molecules - Joshi, Sayali P.; Dutta, Achintya Kumar; Pal, Sourav; Vaval, Nayana (Chemical Physics, 2012)
In this paper we study the harmonic vibrational frequencies, infrared (IR) intensities, Raman intensities and depolarization ratio using extended coupled cluster method. Raman and IR intensities are mixed derivatives of energy with respect to the electric field and geometric perturbation whereas vibrational frequencies are derivatives of energy with respect to geometry. We use semi-numerical approach to obtain these derivatives. We have studied the effect of electron correlation and basis set for the above properties. We compare our results with non-variational coupled cluster and experimental values, wherever available. We have studied HF, BH, CH+, CO and H2CO molecules in different basis sets. For HF molecule, benchmarking is done with full CI values and basis set convergence is studied for this molecule. Effect of triples is studied for all the molecules. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Extended coupled cluster; IR and Raman spectroscopy; Mixed derivatives

Electronic transition dipole moments and dipole oscillator strengths within fock-space multi-reference coupled cluster framework: an efficient and novel approach - Bhattacharya, Debarati; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2013)
Within the Fock-space multi-reference coupled cluster framework, we have evaluated the electronic transition dipole moments, which determine absorption intensities. These depend on matrix elements between two different wave functions (e. g., ground state to the excited state). We present two different ways, to calculate these transition moments. In the first method, we construct the ground and excited state wave functions with the normal exponential ansatz of Fock-space coupled cluster method and then calculate the relevant off-diagonal matrix elements. In the second approach, we linearize the exponential form of the wave operator which will generate the left vector, by use of Lagrangian formulation. The right vector is obtained from the exponential ansatz. In order to relate the transition moments to oscillator strengths, excitation energies need to be evaluated. The excitation energies are obtained from the Fock-space multi-reference framework. The transition dipole moments of the ground to a few excited states, together with the oscillator strengths of a few molecules, are presented. (C) 2013 American Institute of Physics. [http://dx.doi.org/10.1063/1.4793277]

Extended coupled cluster through nth perturbation order for molecular response properties: a comparative study - Gupta, Jitendra; Manohar, Prashant Uday; Ghosh, Aryya; Vaval, Nayana; Pal, Sourav (Chemical Physics, 2013)
In this paper, we have presented and analyzed the extended coupled cluster (ECC) energy functional, truncated up to nth perturbation order in which expansion is limit to operators of the single and double excitations. The expression for the first order energy derivatives based on the above truncation schemes has been derived and numerically analyzed. We have done a comparative study for dipole moment in various perturbative ECC (n) methods (2 <= n <= 5) for three systems (HF, H2O and BH) at equilibrium geometry. We have particularly studied two variants of ECC (4) and ECC (5*) method for stretched geometry. We have analyzed the contribution of important terms present in ECC functional based on perturbative argument. We have compared our results with standard coupled cluster (CCSD) as well as cubic truncated ECC and also benchmarked with the full CI results wherever available. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: Dipole moment; Energy functional; Extended coupled cluster

Electronic transition dipole moment: a semi-biorthogonal approach within valence universal coupled cluster framework - Bhattacharya, Debarati; Vaval, Nayana; Pal, Sourav (International Journal of Quantum Chemistry, 2014)
Electronic dipole strengths (square of transition moments) and oscillator strengths are evaluated for various transitions, arising from the ground state to a few valence excited states. Parallel to two other methods of calculating the dipole strength within the Fock-space multireference coupled cluster framework, a new semi-biorthogonal approach is formulated and implemented in this article. This semi-biorthogonal approach can evaluate dipole strengths at a lower computational effort than the biorthogonal approach without compromising on the accuracy. This new method is compared and tested against the previously developed expectation value and biorthogonal approach for various molecular transitions. (C) 2014 Wiley Periodicals, Inc.
Keywords: electronic transition dipole; Fock-space; oscillator strength; semi-biorthogonal expectation value

Extended coupled cluster method for potential energy surface: a decoupled approach - Joshi, Sayali P.; Vaval, Nayana (Chemical Physics Letters, 2014)
Extended coupled cluster (ECC) method has been implemented extensively for the calculation of molecular properties. In this Letter we report the potential energy surface (PES) study using coupled and a decoupled approximation of ECC. HF, N-2 and C-2 are studied as test systems. N-2 and C-2 being doubly and triply bonded, are considered to be interesting systems for PES study. We compare our results with full CI (FCI) results wherever available. Decoupled approach within ECC framework shows good convergence for all the molecules. (C) 2014 Elsevier B.V. All rights reserved.

Electron attachment to DNA and RNA nucleobases: an EOMCC investigation - Dutta, Achintya Kumar; Sengupta, Turbasu; Vaval, Nayana; Pal, Sourav (International Journal of Quantum Chemistry, 2015)
We report a benchmark theoretical investigation of both vertical and adiabatic electron affinities of DNA and RNA nucleobases: adenine, guanine, cytosine, thymine, and uracil using equation of motion coupled cluster method. The vertical electron affinity (VEA) values of the first five states of the DNA and RNA nucleobases are computed. It is observed that the first electron attached state is energetically accessible in gas phase. Furthermore, an analysis of the natural orbitals exhibits that the first electron attached states of uracil and thymine are valence-bound in nature and undergo significant structural changes on attachment of an extra electron, which reflects in the deviation of the adiabatic electron affinity (AEA) than that of the vertical ones. Conversely, the first electron attached states of cytosine, adenine, and guanine are in the category of dipole-bound anions. Their structure, by and large, remain unaffected on attachment of an extra electron, which is evident from the observed small difference between the AEA and VEA values. VEA and AEA values of all the DNA and RNA nucleobases are found to be negative, which implies that the first electron attached states are not stable rather quasi bound. The results of all previous theoretical calculations are out of track and shows large deviation with respect to the experimentally measured values, whereas, our results are found to be in good agreement. Therefore, our computed values can be used as a reliable standard to calibrate new theoretical methods. (c) 2015 Wiley Periodicals, Inc.
Keywords: DNA-RNA bases; electron affinity; EOMCC

EOMIP-CCSD(2)*: an efficient method for the calculation of ionization potentials - Dutta, Achintya Kumar; Vaval, Nayana; Pal, Sourav (Journal of Chemical Theory and Computation, 2015)
A new approximation within the domain of EOMIP-CC method is proposed. The proposed scheme is based on the perturbative truncation of the similarity transformed effective Hamiltonian matrix. We call it the EOMIP-CCSD(2)* method, which scales as noniterative N-6 and its storage requirement is very less, compared to the conventional EOMIP-CCSD method. The existing EOMIP-CCSD(2) method has a tendency to overestimate the ionization potential (IP) values. On the other hand, our new strategy corrects for the problem of such an overestimation, which is evident from the excellent agreement achieved with the experimental values. Furthermore, not only the ionization potential but also geometry and IR frequencies of problematic double radicals are estimated correctly, and the results are comparable to the CCSD(T) method, obviously at lesser computational cost. The EOMIP-CCSD(2)* method works even for the core ionization and satellite IP, where the earlier EOMIP-CCSD(2) approximation dramatically fails.

Electronic structure parameter of nuclear magnetic quadrupole moment interaction in metal monofluorides - Talukdar, Kaushik; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2020)
The electronic structure parameter (W-M) of the nuclear magnetic quadrupole moment (MQM) interaction in numerous open-shell metal monofluorides (viz., MgF, CaF, SrF, BaF, RaF, and PbF) is computed in the fully relativistic coupled-cluster framework. The electron-correlation effects are found to be very important for the precise calculation of W-M in the studied molecular systems. The molecular MQM interaction parameter scales nearly as Z(2) in the alkaline earth metal monofluorides, where Z is the nuclear charge of metal. Our study identifies (RaF)-Ra-223 as a good candidate for the experimental search of the nuclear MQM, which can help unravel the physics beyond the standard model in the hadron sector of matter.

Effect of charge and solvation shell on non-radiative decay processes in s-block cationic metal ion water clusters - Kumar, Ravi; Ghosh, Aryya; Vaval, Nayana (Journal of Chemical Physics, 2023)
Intermolecular Coulombic decay or electron transfer-mediated decay are the autoionization processes through which a molecule can relax. This relaxation is only possible if the inner valence's ionization potential (IP) exceeds the system's double ionization potential (DIP). To study the effects of charge and solvation shell, we have calculated the IP, DIP values, and lifetime of Na-2s and Mg-2s temporary bound states in various optimized structures of Na+-(H2O)(n) and Mg2+-(H2O)(n) (n = 1-5) micro-solvated clusters, where n water molecules are distributed in a way that some are directly bound to the metal ion and the rest to the water molecules. The first and second solvation shells are the names for the former and the latter water-binding positions, respectively. For a given n, the lifetime of decaying states is longer when water molecules are in the second solvation shell. We found that the Mg-2p state can decay for all n values in Mg2+-(H2O)(n) clusters, whereas the Na-2p state's decay is possible for n >= 2 in Na+-(H2O)(n) clusters. Our findings highlight the influence of metal ions' charge, different solvation shell structures, and the number of water molecules on the decay rate. These systems are relevant to the human body, which makes this study significant.